Analisis Faktor-Faktor Yang Mempengaruhi Struktur Modal Perusahaan Makanan dan Minuman - Kenny Sukardi, Augustpaosa Nariman (Jurnal Ekonomi, 2021)
This study aims to determine the effect of company size, profitability (ROA), Liquidity, Net Profit Margin and Total Asset Turnover on the capital structure of food and beverage companies listed on the Indonesia Stock Exchange for the 2018-2020 research period. The population of the food and beverage sector is 30 companies. The sampling technique used in this research is the purposive sampling method. There are 18 registered food and beverage companies from 2018 to 2020 that meet the criteria to be sampled. The research data used was secondary data which was tested using E-views version 11. The data analysis method used was the multiple regression method. The results of this study indicate that firm size and total asset turnover have a positive effect on the capital structure. Liquidity has a significant negative effect on the capital structure, while profitability and net profit margins have no effect on the capital structure.